Meningkatkan Resiliensi dalam Pendidikan: Peran Mindfulness dalam Menumbuhkan Fleksibilitas Kognitif dan Kekuatan Emosional - Khoiruddin Bashori (SUKMA: Jurnal Pendidikan, 2025)
This article explores the transformative role of mindfulness in strengthening resilience within educational settings, particularly how mindfulness fosters cognitive flexibility and emotional strength—two key traits for adapting to academic and life challenges. Based on research involving students and educators, it concludes that mindfulness not only reduces stress but also enhances emotional regulation, empathy, and adaptive thinking. Integrating mindfulness into the curriculum has been shown to improve student engagement, psychological well-being, and academic performance. By emphasizing emotional intelligence, this article highlights the development of a responsive and inclusive school culture.